2007
DOI: 10.1149/1.2775218
|View full text |Cite
|
Sign up to set email alerts
|

Membrane and Active Layer Degradation upon PEMFC Steady-State Operation

Abstract: We studied proton exchange membrane fuel cell membrane electrode assemblies ͑MEAs͒ degradation after fuel-cell operation. Anode and cathode pronounced degradation was monitored by chemical ͓energy dispersive spectrometry ͑EDS͒, X-ray photoelectron spectroscopy ͑XPS͔͒, physical ͓scanning electron microscopy ͑SEM͒, transmission electron microscopy͔, and electrochemical ͑ultramicroelectrode with cavity͒ techniques. Aged MEAs underwent severe redistribution of most elements ͑Pt, C, F͒, coupled to a dramatic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
115
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 67 publications
6
115
1
1
Order By: Relevance
“…In this mechanism Brownian motion is the driving force, causing surface diffusion of particles with random collisions leading to coalescence [85]. Usually the fact that sintering does not occur significantly in catalysts in the gas phase at temperatures below 500°C is considered to be an indication that coalescence is not the prevailing mechanism [10,83,84]. In recent PEMFC studies it was found that both potential and increased humidity enhance the particle growth [86,87], which favours the dissolution/redeposition mechanism.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In this mechanism Brownian motion is the driving force, causing surface diffusion of particles with random collisions leading to coalescence [85]. Usually the fact that sintering does not occur significantly in catalysts in the gas phase at temperatures below 500°C is considered to be an indication that coalescence is not the prevailing mechanism [10,83,84]. In recent PEMFC studies it was found that both potential and increased humidity enhance the particle growth [86,87], which favours the dissolution/redeposition mechanism.…”
Section: Reviewmentioning
confidence: 99%
“…Still, although both mechanisms lead to an increase in the average particle size with an asymptotic particle size distribution (PSD) the coalescence mechanism has a log-normal distribution (tail at large sizes) and the Ostwald ripening has a tail at the smaller particle sizes but with a maximal particle size cutoff [88]. In many studies a log-normal distribution of Pt particle sizes was found in virgin and used electrodes [10,67,83,86,88]. However, it must be noted that this requires a good sampling also of small particles and results can be affected by the fact that several mechanisms are active at the same time [10,83].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46][47] Synthetic methods of planting Pt in the membrane have been shown to have a detrimental effect on the membrane, 48,49 where platinum ions can act as a Fenton's reaction promoter. 50,51 However, in our group, field operated MEAs with a naturally grown metallic Pt band in the membrane were tested under COCV AST conditions,…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16] According to the report of Rand and Woods, [9] platinum is dissolved above 1.08 V and the evolution of molecular oxygen occurs above 1.46 V, whereas gold is not dissolved at 1.4 V. Dissolved platinum can then either deposit on existing platinum particles to form larger particles (Ostwald ripening) or diffuse into an electrochemically inaccessible portion of the membrane electrode assembly (e.g., into the gas diffusion layer), and the resulting electrochemical active surface area will accordingly decrease. [13,[17][18][19] Shao-Horn and co-workers described a potential mechanism for the loss of electrochemical active surface area. [17] Recently, Adzic and co-workers reported a stabilized platinum catalyst that uses gold clusters for the oxygen reduction reaction.…”
mentioning
confidence: 99%